An Analysis Of Power Struggle In George Orwell’s Novel ‘Animal Farm’ - Faizal, Ahmad (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to analyze the power struggle in George Orwell's novel Animal Farm. The author describes the novel Animal Farm using the historical hermeneutic approach of Wilhelm Dilthey and Roland Barthes' semiotic interpretive method. Research data comes from conflicts between animals and humans and between animals on farms. The data analyzed was taken from reading the novel Animal Farm repeatedly and understanding every element in the story. The author then divides the power struggle based on the tyranny that carries out slavery on the farms. Among them is the propaganda by pigs to rebel against all animals against humans. Animal propaganda is not to imitate and torment humans—and pig animal propaganda is to control the farm personally. The results showed that the power struggle in the form of propaganda and violence was influenced by the difference in ideology to exercise power on the farm. And the conclusion of this study is that George Orwell, through his work, is conducting propaganda and criticizing the ideology of power.